Development of F82H composite materials with a high thermal conductivity. (August 2018) - Chen, Ziwei; Sawa, Y.; Hashimoto, N.
Abstract: Composites of F82H and Fe added with W or Cu wires were sintered by spark plasma sintering in order to improve the thermal conductivity of F82H and pure Fe. W and Cu wires were two-dimensionally distributed on the plane perpendicular to pressure direction during sintering. The composites added with 10vol%Cu and 10vol%W were successfully sintered at 40 MPa at 800 °C and 1000 °C, respectively. The thermal diffusivity of the composites were improved compared to base materials, however, many pores were observed especially in the composites with 10vol%Cu. In order to improve the relative density of the composite of F82H added with 10vol%Cu, the use of smaller powder of both F82H and Cu would be needed. On the other hand, W-based compounds were observed in the composite of F82H added with 10vol%W. This would lead to not only less thermal conductivity but also mechanical property of the composite.